Failure analysis of a broken SA564 stainless steel pump shaft - Hussain, P.B. (Inderscience Publishers, 2021)
Shafts are rotating elements that are subjected to torsion and bending moments that cause failures at times leading to personal injury, capacity loss, or poor product quality if basic preventive design actions are not taken. Against this background, this paper describes the failure analysis and root cause of a broken SA564 grade stainless steel pump shaft used in a plant through visual inspection, metallography, X-ray diffraction, scanning electron microscope, chemical analysis, hardness, tensile and non-destructive tests. The results show that creep, fatigue initiation and propagation from defects in the material during the operation were the predominant factors of pump shaft failure. Moreover, the existence of voids, micro-cracks, sensitisation and creeps were also identified on the broken shaft. Overall, the studied broken shaft of the impeller failed due to fatigue, initiated at the fillet radius of the keyway due to the high cyclic stress loading. Copyright Â© 2021 Inderscience Enterprises Ltd.